2010
DOI: 10.1073/pnas.0914073107
|View full text |Cite
|
Sign up to set email alerts
|

PR65, the HEAT-repeat scaffold of phosphatase PP2A, is an elastic connector that links force and catalysis

Abstract: PR65 is the two-layered (α-α solenoid) HEAT-repeat (Huntingtin, elongation factor 3, a subunit of protein phosphatase 2A, PI3 kinase target of rapamycin 1) scaffold of protein phosphatase PP2A. Molecular dynamics simulations predict that, at forces expected in living systems, PR65 undergoes (visco-)elastic deformations in response to pulling/pushing on its ends. At lower forces, smooth global flexural and torsional changes occur via even redistribution of stress along the hydrophobic core of the molecule. At i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 62 publications
6
116
0
Order By: Relevance
“…Furthermore, an additional distinction of this regulatory loop from the previously described role of PP2A on downstream mTORC1 substrates is that the PP2A holoenzyme responsible for mTORC1 disruption involves the PP2A-Bα (PR55α) subunit rather than the PP2A-B′γ (PR61γ/PP2R5C) subunit implicated in S6K1 dephosphorylation (40). We also found that the association between PP2A-C and mTOR is mediated via the mTOR HEAT repeats, a motif found in Huntingtin, elongation factor 3, A subunit of PP2A, and TOR (41,42). Furthermore, binding of PP2A-C to the activated mTOR mutant L1460P is reduced compared with wild-type mTOR, accounting for the ability of this mutant to rescue mTORC1 signaling in OS cells.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, an additional distinction of this regulatory loop from the previously described role of PP2A on downstream mTORC1 substrates is that the PP2A holoenzyme responsible for mTORC1 disruption involves the PP2A-Bα (PR55α) subunit rather than the PP2A-B′γ (PR61γ/PP2R5C) subunit implicated in S6K1 dephosphorylation (40). We also found that the association between PP2A-C and mTOR is mediated via the mTOR HEAT repeats, a motif found in Huntingtin, elongation factor 3, A subunit of PP2A, and TOR (41,42). Furthermore, binding of PP2A-C to the activated mTOR mutant L1460P is reduced compared with wild-type mTOR, accounting for the ability of this mutant to rescue mTORC1 signaling in OS cells.…”
Section: Discussionmentioning
confidence: 53%
“…The N-terminal HEAT repeats act as a scaffold; they mediate the interactions of ATM and ATR with proteins that regulate their catalytic activity and have an important role in their stability (see poster) (Perry and Kleckner, 2003). The HEAT repeats can also act as elastic connectors that undergo deformation following mechanical stimulation and regulate protein activity (Grinthal et al, 2010). As is the case for other PI3K-family members, PIKKs exist as homo-or heterodimers, and dimerization influences their stability and kinase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Large scale changes in curvature are not uncommon for HEAT repeat structures, as has been shown in a number of molecular dynamics studies. 69,70 Thus, it is likely that the partly disordered SF3b155 region (HEAT repeats) and its interactions with all other SF3b proteins (Fig. 1D) constrains the HEAT repeat structure, thereby, forcing it to take such a peculiar curvature.…”
Section: Sf3b155 -A Highly Curved Heat Repeat Proteinmentioning
confidence: 99%
“…S17), this protein has the ability to act as a "molecular sling shot" in the SF3b complex, utilizing its stored elastic potential energy as a wound spring during the transformation of SF3b from closed to the open state. 69,72 Figure 6. Intrinsically disordered region in the SF3b cryo-EM map.…”
Section: Sf3b -A Fuzzy Complexmentioning
confidence: 99%